2011
DOI: 10.1021/es1035199
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Mg(OH)2Nanoadsorbent during Treating the Low Concentration of CrVI

Abstract: Investigations about how to recycle the deactivated nanomaterials are well-needed. This work was designed to explore the recycling strategy of Mg(OH)(2) nanoadsorbent during treating low concentration of Cr(VI) solution as an example. It was demonstrated that a reversible route between Cr-adsorbed nano-Mg(OH)(2) and Cr-desorbed bulk-MgCO(3) · 3H(2)O can be established by using CO(2) as a phase transformation medium. In each adsorption-desorption cycle, Cr(VI) solution with initial concentration of 10 mg · L(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(63 citation statements)
references
References 31 publications
0
63
0
Order By: Relevance
“…It is also recognized as an excellent material used in wastewater and industrial effluent treatment to absorb heavy metals [6,7] and organic contaminants [8]. Furthermore, the low price and abundant resource make magnesium hydroxide more preferential in many environmental fields compared with sodium hydroxide [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is also recognized as an excellent material used in wastewater and industrial effluent treatment to absorb heavy metals [6,7] and organic contaminants [8]. Furthermore, the low price and abundant resource make magnesium hydroxide more preferential in many environmental fields compared with sodium hydroxide [9].…”
Section: Introductionmentioning
confidence: 99%
“…60,61 The recycling of MGC is important for its industrial application. 14,25 So recycling experiments were executed by washing MGC under magnetic stirring with ethanol (10 ml) for 120 min. Using the recycled MGC as the adsorbent for removal of MB (2.0 Â 10 À5 M, 50 ml) from water, the completed removal of MB was obtained within 60 min, which showed that the adsorption ability of MGC was almost retained after use and recycling (Fig.…”
mentioning
confidence: 99%
“…Magnesium hydroxide, a nontoxic and environmentally friendly chemical product, is widely used in industrial wastewater treatment [1][2][3]. One of the most attractive characteristics of magnesium hydroxide is that it could be recycled and reused [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most attractive characteristics of magnesium hydroxide is that it could be recycled and reused [3]. The recoverability of magnesium hydroxide may significantly reduce the chemical costs and may effectively reduce the threat to human being.…”
Section: Introductionmentioning
confidence: 99%